Steve Jobs and philosophy : for those who think different - Klein, Shawn (Chicago : Open Court, 2015)
"Steve Jobs represents a whole range of values and ideas in pluralistic American culture. He was a barefoot hippy capitalist who did more to change our everyday lives than anyone since Thomas Edison. Coming from modest means and education, he revolutionized several key industries and became fantastically wealthy. In Steve Jobs and Philosophy 16 philosophers examine the inspiring yet often baffling world of Steve Jobs. What can we learn about business ethics from his example? What are the major virtues of a creative innovator? How could Jobs defy conventional business practices? How did he combine values and attitudes previously believed to be unmixable? What does it really mean to "think different"? Can entrepreneurs be made or are they just born? If Jobs didn't make any major inventions, what was his contribution? What does Jobs teach us about the notions of simplicity and functionality in design? How do Jobs's achievements alter the way we think about technology in relation to human life? Steve Jobs and Philosophy covers vital issues in ethics, business, aesthetics, and technology. It includes a fascinating appendix listing all the philosophers mentioned in the book, along with explanations of their lives and key themes in their thoughts. "--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Jobs, Steve, -- 1955-2011.; Business ethics; Entrepreneurship -- Moral and ethical aspects; Technological innovations -- Moral and ethical aspects; Electronic books